2001
DOI: 10.1038/emm.2001.6
|View full text |Cite
|
Sign up to set email alerts
|

F508 amino acid deletion mutation of CFTR gene in Korean lung cancer patients

Abstract: Mutations of the transmembrane conductance regulator (CFTR) gene in cystic fibrosis lead to dysfunction of the lung, pancreas, and sweat glands, etc. To investigate the possibility of the relationship between lung cancer and the mutations of CFTR gene, we determined amino acid sequences using reverse transcription-polymerase chain reaction (RT-PCR) and DNA sequencing. In this study, the deletion mutation of 508th amino acid in one of nine lung caner patients was found confirming that CFTR gene mutation exists … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…A large cohort study conducted by Neglia et al [32] demonstrated that the genetic variation of the CFTR gene is associated with a moderate increase (1.4 fold) in the risk of lung cancer, and CFTR gene mutation has been reported in lung cancer patients [50,51] . Epigenetic modifications such as DNA methylation regulate gene expression to maintain cell growth and development.…”
Section: Cftr and Other Cancersmentioning
confidence: 99%
“…A large cohort study conducted by Neglia et al [32] demonstrated that the genetic variation of the CFTR gene is associated with a moderate increase (1.4 fold) in the risk of lung cancer, and CFTR gene mutation has been reported in lung cancer patients [50,51] . Epigenetic modifications such as DNA methylation regulate gene expression to maintain cell growth and development.…”
Section: Cftr and Other Cancersmentioning
confidence: 99%
“…Meanwhile, mutations and lowpenetrance polymorphisms in the CFTR gene have been found in patients with various cancers, including pancreatic cancer [6][7][8][9][10], melanoma [11,12], breast cancer [12,13], colon cancer [12], and lung cancer [14,15]. Prostate cancer has been reported in CF patients [16] and atypical CF patients [17], and the incidence seemed to be lower than expected [16].…”
Section: Introductionmentioning
confidence: 99%
“…Nonfunctional CFTR has been suggested to suppress tumor growth and proliferation [21]. Mutations and polymorphisms in CFTR gene can cause failure of CFTR, therefore may be involved in the pathogenesis of some cancers [6][7][8][9][10][11][12][13][14][15][16]. It has been suggested that interactions between CFTR polymorphisms and environmental factors might play a role in the development of pancreatic cancer [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…However, gradual changes in DNA methylation occur with age [ 102 ]. Of note, hypermethylation of CFTR or the F508del CFTR has been suggested as a tumour risk biomarker for young CF patients [ 100 , 103 ].…”
Section: Cellular Senescence Is Associated With the High Risk Of Cancmentioning
confidence: 99%